Prediksi Distribusi Sedimentasi Terhadap Usia Guna Waduk Ameroro, Sulawesi Tenggara - Indradjati Rachmatullah; Dantje Kardana Natakusumah; Widyaningtias Widyaningtias; Arno Adi Kuntoro; Eka Oktariyanto Nugroho; Agung Permana; Herdy Setiawan; Dyah Widyaningrum (Journal on Education, 2024)
The Ameroro River experiences significant sedimentation rates from year to year, along with rapid land cover changes. Due to the considerable benefits of the Ameroro River for the sustainability of life in Konawe Regency, it was decided to construct the Ameroro Reservoir as a means to fulfill irrigation needs and provide raw water for the community. Given the high sedimentation in reservoirs in Indonesia, it rapidly accelerates the aging of the Reservoir. One of the issues is the inadequate representation of sediment distribution in the reservoir, reducing the effectiveness of sediment control and management in the Reservoir. Predictions using HEC-RAS 2D reveal the sediment distribution in the Ameroro reservoir at locations STA 13872 in the upstream river and STA 4446 at the inlet, which is 7.7 km from the main river length from the Reservoir's axis and 4.5 km from the inlet river length. Sedimentation rates, based on riverbed material modeling and land cover, show an influx of sediment into the reservoir at 1,192,015 m3/year, comprising 662,275 m3/year from the upstream river and 529,739 m3/year from the inlet river. Calculations using the sedimentation deposition composition method and Brune's trap efficiency method indicate that the original Reservoir's lifespan of 107 years will be reduced to 85 years, deviating by 22 years from the plan. This implies that the Reservoir will reach the end of its useful life sooner than anticipated.